The use of functional activities in therapy: An integration of the principles of motor control and the learning process - E. S. Bakkes; S. J. Groenewald; J. R. Hughes (AOSIS, 1996)
The successful rehabilitation of a patient following a CVA is largely dependent on the effective relearning of previous motor skills or the learning of new skills. An understanding of the components of motor function and control and the principles of the learning process is therefore essential. Functional activities may be used as an optimal means of combining these principles so as to improve the efficacy of physiotherapy treatment. Two case studies are used to illustrate this approach.